Stress ulcer prophylaxis in the Intensive Care Unit: an integrative review (Research, Society and Development, 2021)
Stress ulcers (SU) are a common complication in patients admitted to intensive care units (ICU), which are defined as upper gastrointestinal tract ulcers, and some forms can evolve to hemorrhage. Given the hemodynamic consequences caused in patients with SU in the context of the intensive care unit, this article aims to investigate pathophysiological causes, prophylaxis and therapies to avoid bleeding risks. This is a bibliographical and exploratory review study using the integrative literature review method, carried out in the PUBMED, EMBASE and LILACS databases, using the descriptors/key words: "Stress Ulcer" AND "Intensive Care Unit". Initially, the search returned 1,074 works, after applying the inclusion and exclusion criteria, seven were selected for this study. It was observed that patients on mechanical ventilation for more than 48 hours, coagulopathy, shock, renal failure with hemodialysis, history of peptic ulcer, previous upper digestive hemorrhage, multiple trauma, septic and liver failure, have an increased risk of 3600% for developing EU. Prophylaxis should be carried out individually and following specific recommendations for the local population, to avoid errors, misuse of antibiotics and inadequate prior withdrawal. It is noteworthy that there are few randomized studies that assess the therapeutic efficacy of SU prophylaxis in Brazil, requiring further studies for evaluation directed at the Brazilian population.